1995
DOI: 10.1172/jci118232
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cell injury by oxidized low density lipoprotein involves lipid hydroperoxide-induced formation of alkoxyl, lipid, and peroxyl radicals.

Abstract: Mounting evidence supports current theories linking lipoprotein oxidation to atherosclerosis. We sought the cellular biochemical mechanism by which oxidized LDL inflicts cell injury. Inhibitors of candidate pathways of cell death were used to treat human fibroblast target cells exposed to oxidized LDL. Ebselen, which degrades lipid hydroperoxides, inhibited oxidized LDL toxicity, consistent with our recent report that 7f8-hydroperoxycholesterol (7fi-OOH chol) is the major cytotoxin of oxidized LDL. Intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 63 publications
5
41
0
Order By: Relevance
“…It has even been suggested that cholesterol might be a stabilizer of lysosomal membranes in cells of atherosclerotic lesions, thus preventing the relocation of lysosomal enzymes. 33 However, based on our data and those of others, 34,35 we conclude that the effect of lipoprotein cholesterol on lysosomal stability is largely dependent on the physicochemical status of the former. If the lipids are oxidized, the resulting oxysterols, hydroperoxides, and their toxic carbonylic fragments may affect lysosomal enzymes and membranes, whereas nLDL or AcLDL would not.…”
Section: Discussionsupporting
confidence: 70%
“…It has even been suggested that cholesterol might be a stabilizer of lysosomal membranes in cells of atherosclerotic lesions, thus preventing the relocation of lysosomal enzymes. 33 However, based on our data and those of others, 34,35 we conclude that the effect of lipoprotein cholesterol on lysosomal stability is largely dependent on the physicochemical status of the former. If the lipids are oxidized, the resulting oxysterols, hydroperoxides, and their toxic carbonylic fragments may affect lysosomal enzymes and membranes, whereas nLDL or AcLDL would not.…”
Section: Discussionsupporting
confidence: 70%
“…Cells made quiescent by 48 h of serum deprivation were exposed to oxidized LDL, lysoPC, or serum and [ 3 H]thymidine incorporation was measured as a function of time. Although as expected the response of cells to oxidized LDL or lysoPC was not of the same magnitude as that of cells exposed to serum (9), the time course of thymidine incorporation was the same as after serum stimulation; that is, the peak thymidine incorporation occurred at approximately 28 h from the addition of oxidized LDL, lysoPC, or serum (data not shown). Thus, cells responded temporally to oxidized LDL or lysoPC as they respond to known mitogens.…”
Section: Resultssupporting
confidence: 54%
“…Oxidized LDL induces certain genes (1,2), suppresses others (3)(4)(5), alters cellular lipid metabolism (6), and injures cells (7)(8)(9). Because oxidized LDL has been shown to reside in arterial lesions in animals and humans (10), the alterations in cell function observed in vitro have been suspected of involvement in vascular lesion development (11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms have been proposed to explain this effect, including enhanced uptake of Ox-LDL by macrophages, chemotactic potential for circulating monocytes, inhibition of the motility of tissue macrophages, and alteration of the coagulation pathways [16,19]. Ox-LDL has been shown to be cytotoxic to various cells such as vascular cells, monocytes and macrophages [20,21] by mechanisms not yet sufficiently characterized. It does seem conceivable, however, that Ox-LDL may exert some of its deleterious effects, owing to its immunogenicity, with the resultant formation anti-Ox-LDL antibodies and generation of immune complexes.…”
Section: Introductionmentioning
confidence: 99%